Self-Confidence and Speaking Skills: Is there Any Significance Correlation? - Satria Budi Wiguna, Kadek; Ari Wiryadi Joni, Dewa Ayu; Mantra, Ida Bagus Nyoman (Journal on Studies in English Language Teaching (JOSELT), 2025)
The present study which made use of an ex-post facto research with correlation design was intended to figure out the significant correlation between self-confidence and speaking skills of the eighth-grade students of SMP N 4 Mengwi in the academic year 2024/2025. The samples of the research consisted of 63 students which were chosen by means of cluster sampling method with lottery system. The data were collected through administering the research instruments which were in the form of questionnaire and role-play. The obtained data were statistically analysed by using Normality Test, Homogeneity Test, Pearson product moment correlation and T-test. Then the result of correlations is 0.93, which means the data > 0.05, it showed that the data was had high correlations. The results of the data analysis clearly revealed the alternative hypothesis was accepted. In other words, the research findings confirmed that there is significant correlation between self-confidence and speaking skills of the eighth-grade students of SMP N 4 Mengwi in the academic year 2024/2025.